BOARD DIVERSITY ON FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Ibrahim, Zahra; Kabir, Auwal Muhammad; Sani, Saidu (Kashere Journal of Management Sciences, 2024)
This study examines the impact of board diversity on financial performance of listed deposit money banks in Nigeria. The study adopted ex-post facto research design and collected data using secondary method from published annual reports of the selected banks in Nigeria. The population of this study was 14 listed deposit money banks in Nigeria where the entire population was considered as the sample using census sampling technique. The data gathered were analyzed using descriptive and inferential statistics such as correlation and multiple regression with the help of STATA version 14. The study found that age diversity and expertise diversity have significant positive influence on financial performance while gender diversity has significant negative relationship. In view of the findings of the study, it was recommended that banks should imbibe the culture of diverse age in their boardroom to navigate the contemporary economic dynamisms as a result of business globalization. Also, it was suggested that authorities in Nigerian banking industry should limit the increased women on the board because they have always been marginalized as rubber stamp of their men counterpart and has not brought any improvement in the system. Finally, the study advised that, greater measures should be taken by deposit money banks to ensure that certified financial or any other professional expert stay longer on the boards to guarantee improved performance in the short and long run